Keynesian economics. - Timlin, Mabel F. (Mabel Frances) (University of Toronto Press, 1942)
It is the intention in this study to explore the system of economic analysis set out in its original form in Mr. John Maynard Keynes' The General Theory of Employment, Interest and Money in order to consider first its internal consistency and second its application to the world we know.
"The book developed from a doctoral dissertation ... accepted in July, 1940, by the University of Washington."--Preface
Keywords: Keynes, John Maynard, -- 1883-1946. -- General theory of employment, interest and money.; Keynes, John Maynard, -- 1883-1946 -- General theory of employment, interest, and money.; General theory of employment, interest and money (Keynes, John Maynard); Economics.; Money.; Interest.; Keynesian economics.; Usury.; Economics; Économie politique.; Monnaie.; Intérêt (Économie); Keynésianisme.; Usure.; economics.; money (objects); BUSINESS & ECONOMICS -- Economics -- General.; BUSINESS & ECONOMICS -- Reference.; BUSINESS & ECONOMICS -- Economic History.; Usury; Keynesian economics; Interest; Money; Keynessche Theorie